PENINGKATAN INOVASI KULINER LOKAL DESA WISATA KOTA SEMARANG - Tuwuh Adhistyo W; Krisnawati Setyaningrum N; Aletta Dewi Maria (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
This community service activity helps managers of tourist villages in the city of Semarang aim to help increase local culinary innovation in the city of Semarang and create new menu creativity and be able to provide significant changes for the better. This activity was carried out on March 1, 2019 at the smart home of the Kandri Tourism Village, Semarang, which was attended by 30 people consisting of tourism village managers in the city of Semarang. The conclusion of this community service activity is that participants' knowledge of local culinary innovations increases, participants are able to repair and upgrade packaging to attract consumer interest, and participants are able to apply what was given during the training.